Infectious disease and boxing - King, O. S. (Clinics in Sports Medicine, 2009)
There are no unique boxing diseases but certain factors contributing to the spread of illnesses apply strongly to the boxer, coach, and the training facility. This article examines the nature of the sport of boxing and its surrounding environment, and the likelihood of spread of infection through airborne, contact, or blood-borne routes of transmission. Evidence from other sports such as running, wrestling, and martial arts is included to help elucidate the pathophysiologic elements that could be identified in boxers.